Sistem Informasi Manajemen Anggaran Keuangan dan Pendapatan Perusahaan Berbasis Web Pada PT. Arelosoft Inovasi Dunia - Martin Siregar; Sholihin (CV. Multi Kreasi Media, 2022)
PT. Arelosoft Innovation World is a computer hardware and software development company. This company is professional in handling various consultations from clients to develop computer software and hardware. The financial and revenue budget management process in this company has a complex phase and is carried out offline, management is carried out by managers, supervisors and document or report makers (operators), in the initial phase the manager makes an order for supervisors to carry out financial budgeting and recording income for a certain period of time, after which the supervisor follows up and conveys to the operator the last operator made and then submitted validation to the supervisor. In the management process, errors in information often occur, the level of consistency in budgeting is decreasing, and there is no budget monitoring system yet. The purpose of this research is to make the Financial and Revenue Budget Management Information System able to carry out all phases of management carried out by managers, supervisors and operators online with web-based applications, this system is designed using the laravel framework and the php, javascript and vuejs programming languages. The information system that has been produced in this design can manage data on financial and income budget needs while designing financial and income budget data, this system will also provide export data in the form of report documents or attachments